Analisis Pengendalian Kualitas Part In House Box Fuel Inlet Pada Proses Stamping Dengan Menggunakan Metode Six Sigma Untuk Mengurangi Biaya Rantai Pasok (Studi Kasus PT. DPM) - Purnamasari, Hylda Kusuma; Poncotoyo, Wahyu; Sitorus, Purbanuara Parlindungan (Jurnal Sistem Transportasi & Logistik, 2024)
PT. DPM is a manufacturing company engaged in the production of bodies, motorcycle spare parts (2 wheels) and cars (4 wheels). The company handles several types of parts on cars focused on the stamping area, in this study analyzing part quality control in the Box Fuel Inlet sub-group. During the production process there are known problems, namely the existence of defects or defects in the accuracy of clearance or gaps. This shows that the quality of goods is not optimal in the Box Fuel Inlet sub-group. For this reason, it is necessary to carry out an analysis of quality control in order to be able to reduce the number of defects or to produce zero defects. The method used in this study uses Six Sigma with DMAIC (Define, Measure, Analyze, Improve and Control) stages and to determine critical points or failure modes with the highest risk value to provide recommendations or recommended actions. The results showed that the highest defect was found in the D30 Fuel Inlet Box with a total defect of 31 pcs. The Capability Process (CP) calculation shows that the three Box Fuel Inlet sub-groups are below the normal limit